Pengaruh Pemberian Dosis Campuran Pupuk Organik Cair Paitan dan Air Kelapa terhadap Pertumbuhan Tanaman Kacang Hijau (Vigna radiata. L) - Muharama Yora; Aulia Meyuliana; Friza Elinda; Anggi Wulandari; Wurwatil Azizah; Rahmat Syahbandi; Adel Eka Putra; Sherly Indri Selviana; Puji Julio; Lega Hidayatul Suci; Febi Fran Pratama (Eduscience Development Journal, 2022)
Research on the effect of given a mixtured of Paitan Liquid Organic Fertilizer and Coconut Water on the Growth of Mung Beans (Vigna radiata. L) was carried out in Halaban-Panyakalan, Kec. Kubung, Solok Regency, West Sumatra, in July-August 2021. The study aims to determined the effect of giving various doses of POC paitan and coconut water on the growth of mung bean plants. The method used was a Randomized Block Design (RBD) which consisted of 4 groups, 6 treatments and there were 6 plants for each treatment so that 144 experimental units was obtained. The dose of liquid organic fertilizer + coconut water given in each treatment was 0 ml (0 ml POC paitan + 100 ml coconut water); 10 ml (10 ml POC paitan + 90 ml coconut water); 20 ml (20 ml POC paitan + 80 ml coconut water); 30 ml (30 ml POC paitan + 70 ml coconut water); 40 ml (40 ml POC paitan + 60 ml coconut water); and 50 ml (50 ml POC paitan + 50 ml coconut water). The research data was analyzed for variance if the calculated F was greater than F table 5%, followed by Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. Parameters observed in the study was plant height (cm), number of leaves, stem diameter (cm), leaf length (cm), leaf width (cm) and flowering age. Based on the results of the research that was done, it can be concluded that the application of a mixture of Paitan liquid organic fertilizer and coconut water has a significant effect only on the character of plant height. The character of the number of leaves, stem diameter, leaf width, leaf length and age of flowering had no significant effect. The highest average plant height was found in P5 treatment, which was a mixtured of 50 ml of POC paitan and 50 ml of coconut water of 14.23 cm. In other characters, the highest average was found in the P3 treatment, which was a mixture of 30 ml of POC paitan and 70 ml of coconut water.